The volume distribution of artificial aurora induced by HF radio waves in the ionosphere - Kvammen, Andreas (UiT Norges arktiske universitet, 2016)
This thesis presents three-dimensional modelling of artificial aurora in the ionospheric F layer, induced by high frequency (HF) O-mode radio waves from the EISCAT heating facility. Understanding how HF radio waves produces enhanced emission in the ionosphere has been one of the one of the major motivations for conducting heating experiments during the last decades. A key element for understanding the heating process is to accurately determine the RIOE (Radio Induced Optical Emission) volume distribution. There are two main theories explaining the RIOE, the accelerated electron excitation theory and the thermal electron excitation theory. Three different auroral construction techniques were considered, theoretical, semi-theoretical and free parameter search. The theoretical modelling is based on accelerated electron excitation theory predictions. Projections of the three dimensional models were compared to observational images of the artificial aurora, taken at the Auroral Large Imaging System (ALIS) in northern Sweden. ALIS takes simultaneous images of the RIOE at four separate ground based imaging stations. This allows tomographic-like reconstruction of the artificial aurora. The ALIS images were taken with different filters, providing auroral modelling of the 5577 Å, 6300 Å and 8446 Å emission lines. It was clear, by comparisons between the observational images and the projections of the modelled aurora, that the semi-theoretical and free parameter search modelling provided physically sound and statistically feasible constructions of the artificial aural. Whereas the theoretically modelled aurora projections did not agree with the observational images.